Sistem Peringatan Kebakaran Multisensor Berbasis Mikrokontroller - Alauddin Y; A. Muh. Batara Ramadhan (Fakultas Teknik Universitas Muhammadiyah Parepare, 2025)
This research aims to design a microcontroller-based multisensor fire warning system. The main objective of this microcontroller-based fire warning system is to increase the speed and accuracy of early fire detection. Using quantitative research methods based on research and deployment by testing the function of a series of tools as expected and referring to previous literature studies that have been collected. The test results are analyzed to see the accuracy and speed of the sensor responding when there is a fire and providing a warning via speaker.